Personality, Job Crafting, and Performance in Select Public Sector Employees in India - Varma, Rushil; Sharma, Archana; Rath, Namita; Sahai, Alok Kumar (Prabandhan: Indian Journal of Management, 2024)
Purpose : The present study focused on establishing the relationship between the dark and bright sides of personality on job performance. The study also investigated the mediating role of job crafting on job performance in selected public sector undertakings. Methodology : A self-reported questionnaire containing 63 questions was used to collect data from 650 respondents in Lucknow and Bhubaneswar. The interrelationships between the dark and bright sides of personality, job crafting, and work performance were established using structural equation modeling on SPSS 23/AMOS 18 software. Findings : The predictive value of the Big Five model of personality was established in our study by a positive and significant direct relationship between organizational citizenship behavior (Î² = 0.38) and mediated value through job crafting (Î² = 0.11). The predictive value of the dark triad was shown to have a positive and significant relationship with counterproductive work behaviour (Î² = 0.23) and a mediated value through job crafting (Î² = 0.09). Practical Implications : Organizational performance depends on the bright and dark aspects of personality, and human resource departments can use personality profiling for better work output. Originality : Unlike prior research on the effect of personality type on job performance, the present work included the added dimension of mediated effects of job crafting on job performance, besides the direct effects of the dark and bright sides of personality.